Investigation of the Teachers’ Restraint and Satisfaction Perceptions in their Free Times - Yönet, Engin; Çalık, Fehmi; Soyer, Fikret; Samar, Ezgi; Ece, Cuma; Seviç, Meliha (Asian Journal of Education and Training, 2019)
In this study it was intended to investigate the Boredom and satisfaction perceptions of the teachers who participate / do not participate in recreational activities during their leisure time in Konya. The screening model was used in the study. 330 questionnaire forms were distributed to the participants. As the result of the review, 300 of the questionnaires were found to be worth for analyzing after excluding those which were invalid due to the following reasons marking the same options or leaving the questionnaire incomplete. The information of 300 participants (46,7% male n=140, 53,3% female n=160) were taken into consideration. The Leisure Boredom Scale whose Turkish adaptation was made by Kara, Gürbüz and Öncü was used as data collection tool in the research. The boredom and satisfaction perceptions of the participants in their leisure time were evaluated in terms of the age, gender, income level and the frequency of participation. In the study significant difference was observed at the significance level in the leisure boredom perception according to variables age, gender and the frequency of participation. In terms of these variables significant difference was not observed in the satisfaction perceptions. On the contrary, in terms of the income level variable while significant difference wasn’t observed in the leisure boredom perception, in the satisfaction perception significant difference was observed. At the participation point of the educational administrators and teachers in leisure time activities contribution can be ensured to the satisfaction perception against the boredom with the necessary planning and implementing possibilities.